연소 배출가스 중 SO₂ 농도에 따른 응축성먼지 변화에 관한 연구 - 유정훈(JeongHun Yu); 임슬기(SeulGi Lim); 송지한(Jihan Song); 이도영(DoYoung Lee); 유명상(MyeongSang Yu); 김종호(JongHo Kim) (한국대기환경학회지(국문), 2018)
Particulate matter (PM) emitted from fossil fuel-combustion facilities can be classified as either filterable or condensable PM. The U.S. Environmental Protection Agency (EPA) defined condensable PM as material that is in the phase of vapor at the stack temperature of the sampling location which condenses, reacts upon cooling and dilution in the ambient air to form solid or liquid in a few second after the discharge from the stack. Condensable PM passed through the filter media and it is typically ignored. But condensable PM was defined as a component of primary PM. This study investigates the change of condensable PM according to the variation in the sulfur dioxide of combustion gas. Domestic oil boilers were used as the source of emission (SO2) and the level of SO2 concentration (0, 50, 80, and 120 ppm) was adjusted by diluting general light oil and marine gas oil (MGO) that contains sulfur less than 0.5%. Condensable PM was measured as 2.72, 6.10, 8.38, and 13.34 mg/m3 when SO2 concentration in combustion gas were 0, 50, 80, and 120 ppm respectively. The condensable PM tended to increase as the concentration of SO2 increased. Some of the gaseous air pollutants emitted from the stack should be considered precursors of condensable PM. The gas phase pollutants which converted into condensable PM should reduced for condensable PM control. KCI Citation Count: 0